Molecular Bases of Human Papillomavirus Pathogenesis in the Development of Cervical Cancer - Pedroza-Saavedra, Adolfo; Plett-Torres, Tanya; Chihu-Amparán, Lilia; Maldonado-Gama, Minerva; González-Jaimes, Ana M.; Esquivel-Guadarrama, Fernando; Gutiérrez-Xicotencatl, Lourdes (IntechOpen, 2012)
None